Progress and challenges in achieving an evidence-based education policy in Latin America and the Caribbean - Miguel Urquiola (Latin American Economic Review, 2015)
This paper reviews the progress economists have made towards achieving an evidence-based educational policy, and highlights challenges that remain. The five main findings are: (1) over the past two decades, much effort has gone into identifying the causal effects of school inputs; this work has produced results and should be expanded. (2) That said, particularly when it originates in small-scale experiments, such work is unlikely to produce a full road map for an evidence-based education policy. (3) There has been less work on the effects of educational inputs at the pre-school stage, and this may be a greater constraint to sound policy than at first appears. (4) There has also been progress on understanding the effects of incentives within education. (5) There is relatively less work surrounding the effects of inputs provided by parents and students, both in terms of resources and effort.
Keywords: I2; 330; Education policy; Developing countries